Acute ischemic stroke as a rare complication of steroid resistant nephrotic syndrome in adolescent: A case report - Bahar, Ashari; Akbar, Muhammad; Basri, Muhammad I. (Journal of Case Reports in Dental Medicine, 2022)
AbstractIschemic stroke is an uncommon complication of nephrotic syndrome, but must be adressed appropriately, because of the significant health impact. We reported a case of 17-years old male with sudden onset right hemiparesis. The patient was previously diagnosed with steroid resistant nephrotic syndrome (SRNS), and was treated with pulsed cyclophosphamide. Laboratory examination showed proteinuria, hypoalbuminemia and high low density lipoprotein. Axial head CT scan showed infarction in left basal ganglia and corona radiata. Digital substraction angiography (DSA) confirmed severe stenosis in the left middle cerebral artery. The patient was treated with antiplatelet, along with treatment for SRNS and hypercholestrolemia. SNRS might increase the risk of early occurrence of stroke in young adult, throught acceleration of atherosclerosis and hypercoagulable state.